EFFECTS OF STRETCHING TRAINING ON LOWER LIMB EXPLOSIVE STRENGTH IN FIGURE SKATING ATHLETES - Mochida,Miho (2023)
ABSTRACT Introduction Figure skating is characterized by a high degree of flexibility, balance, and technical precision. It belongs to the sports group that combines high speed and endurance. Therefore, it is very important for athletes to correctly master these techniques and physical strength and execute precise movements in their performances. Objective Explore the effect of stretching training on the lower limb explosive strength of figure skating athletes. Methods 20 outstanding male figure skaters from the Chinese team were selected as volunteers. The experimental method was used using the OPTOJUMP test system, among other instruments, for comparison of pre and post-intervention results. Results Through scientific observation, it was found that skaters have less requirement for upper limb strength training, minimizing its importance because upper limb strength training can assist in motor coordination of athletes’ lower limbs and help them stabilize to perform dynamic movements. Therefore upper limb strength training is also emphasized in the proposed training. Conclusion The stretching training on the lower limb strength of figure skating athletes proved to be useful for the improvement of performance and execution of the intrinsic movements of the sport. Level of evidence II; Therapeutic studies - investigation of treatment outcomes.